A comparison of different filters for white cell reduction - Yaprak, Işın; Yercen, Nermin; Akşit, Sadık; Akdeniz, Figen; Türker, Meral; Çağlayan, Suat (The Turkish Journal of Pediatrics, 1998)
Removal of white blood cells (WBCs) from blood components before transfusion by filters with at least 3 \log_{10} depletion may prevent or delay leukocyte-associated transfusion reactions such as HLA alloimmunization, non-hemolytic febrile reactions, transmitted infections (e.g., CMV, HTLV-1), and immunomodulation. The aim of this study was to compare the leukocyte removal efficiency (LRE) of six commercial bedside filters that are said to achieve 3 \log_{10} (Bio R-01, Leucostop 4LT-1, Pall RC 50) and 4 \log_{10} (Bio R-01 Plus, Pall RC 400, Pall RC XL-1) WBC depletion. A total of 430 units of whole blood ranging from 32 to 92 for each filter type were analyzed by an automated counter before and after filtration. Postfiltration blood samples were also evaluated for WBCs by Nageotte chamber. All the filters demonstrated leukocyte removal about 1 \log_{10} less than the manufacturer’s claim. The fourth generation filters showed a better performance than the third generation filters. Of them, Pall RC XL-1 showed the best efficacy with 99.93 percent leukocyte removal and a median residual WBCs of 1.6 × 10^6 per unit. These results indicate that the fourth generation filters, which are designed for the filtration of packed red cells, in particular Pall RC XL-1, are also able to reduce WBCs from whole blood below the critical antigenic leukocyte load ( 5 × 10^6 ), and can be efficiently used for polytransfused patients to prevent alloimmunization.
Keywords: leukocyte removal efficiency; bedside filters; thalassemia; allimmunization; blood transfusion